Efficiency of Financing in Sharia Cooperatives - Djaka Badranaya (ETIKONOMI, 2017)
Efficiency is one of the performance’s indicator in sharia cooperatives. This study uses data envelopment analysis (DEA) method to measure the efficiency of financing sharia cooperatives. DEA is one method of measuring efficiency using frontier analysis that has proven its use. Samples to be used are KJKS Kota Bambu Utara (KBU) and Kota Bambu Selatan (KBS). On average, KJKS KBU has a value high enough efficiency reached 98.7%. Meanwhile, KJKS KBS achieve 100% efficiency. This research has an important role in optimizing the efficiency of sharia cooperative, so that its presence can provide great benefits to society.DOI: 10.15408/etk.v16i2.5437